Technology Readiness and Flow Theory Influence Toward Acceptance of Augmented Reality Among Students in Private Universities in Jakarta, Indonesia - Budi, Arifitama (2024)
Students today benefit from various tools that enhance their learning, including digital platforms, online courses, and virtual classrooms, with augmented reality (AR) becoming increasingly popular. However, in Indonesia, most AR research in higher education focuses on software development rather than assessing students' technology readiness and acceptance. This impacts their motivation and effectiveness in using AR for learning. The level of technology readiness of students will affect their acceptance, and motivation to learn using AR in education that affects focus and academic achievement. This study examined how technology readiness and flow theory affect augmented reality acceptance in Jakarta's private higher education institutions. The Technology Acceptance Model supported this study and also integrated the Technology Readiness Index and Flow Theory to examine how readiness and motivation affect student uptake of augmented reality. This research uses Mixed Method Design to gather, analyse, and validate quantitative and qualitative data. A total of 602 students from 20 private universities in Jakarta is acquired to the survey questionnaire as a basis for the quantitative analysis using SmartPLS, then followed by qualitative research from a total of 10 students as a respondent to validate the quantitative findings using Nvivo12. Based on the results, three variables were rejected in the Technology Readiness Index: Optimism (OPT) towards Perceived of Usefulness (PU) and Perceived Ease of Use (PEOU), and Discomfort (DIS) towards Perceived Usefulness (PU) towards AR acceptance. The Technology Acceptance Model accepts all variables that significantly affect augmented reality acceptance, including Perceived Ease of Use (PEOU) towards Perceived of Usefulness (PU) and Attitude Towards Using (ATU), PU towards Intention to Use (IU) and Attitude Toward Using (ATU), and Attitude Toward Using (ATU) towards the intention to Use (IU). Lasty, Enjoyment, Control, and Concentration towards the Intention to Use in the Flow Theory are accepted. The result of the qualitative research confirmed that the findings in the quantitative results are valid. The implication of these findings for private universities should focus on other factors like innovation, insecurity, and control that significantly impact AR acceptance. Recognizing that readiness and motivation play crucial roles in AR acceptance, institutions should develop strategies to boost students' confidence and interest in using AR technology.